Struktur modal sebagai intervening faktor Pada determinan harga saham perusahaan Sektor otomotif di bursa efek indonesia - Maryam Monika Rangkuti (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
This study aims to determine how the role of capital structure as an intervening factor on the effect of profitability on the stock prices of automotive sector companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. This study uses an associative approach. Data collection techniques in this study using documentation techniques. The data analysis technique in this research is using path analysis. The results of this study indicate that Profitability (Return On Equity) has no significant effect on Capital Structure (Debt To Equtity Ratio), Profitability (Return On Equity) has a significant and positive effect on Stock Prices, Capital Structure (Debt To Equtity Ratio) has no significant effect on Stock Prices. , and Profitability (Return On Equity) directly affects Stock Prices and Capital Structure (Debt To Equtity Ratio) is not an intervening variable in automotive sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period.